Historical Evolution of Surgery for Transposition of Great Arteries (TGA) - Suraj Wasudeo Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
The science and art of cardiac surgery has made rapid development in the past 65 years. The surgery for transposition of great arteries (TGA) symbolises the manner in which cardiac surgery has progressed. The eventually successful solution in the form of the now popular arterial switch operation (ASO) was elucidated after multiple contributions from several surgical stalwarts and geniuses over more than 35 years (Figure 1). This review traces the various milestones along this journey. The first morphological description of TGA can be credited to Baillie in 1797 [1], while the term 'Transposition of Great Arteries' was used for the first time by Farre in 1814 [2]. Though the term 'transposition' was used aberrantly in literature till 1970, the ambiguity was resolved by Van Praagh et al., in 1971 who said that, it refers to the aorta and pulmonary artery (PA) being displaced across the ventricular septum [3].